The Role of Value Internalization in Suppressing the Level of Youth Aggressiveness: An Empirical Study of IKS.PI Kera Sakti Silat College - Ahmad Helmy Fauzan; Wahyu Widiantoro (Psikostudia : Jurnal Psikologi, 2025)
The high tendency of aggressive behavior in adolescents is an issue that needs attention, especially when positive values are not strongly embedded in individuals. In this context, the teaching values of the IKS.PI Kera Sakti martial arts college have the potential to be one of the sources of positive character building. This study aims to examine the relationship between the internalization of IKS.PI Kera Sakti martial arts values and the level of aggressiveness in adolescents. The approach used is quantitative with the subjects as many as 63 teenagers who are active members of the martial arts college. The sampling technique used Purposive Sampling. The data collection method was carried out using a value internalization scale and an aggressiveness scale. The data that has been collected is then analyzed with the Pearson Product Moment analysis test. The results showed a Pearson correlation value of -0.599 with a significant value of 0.000 (p <0.05). Data analysis showed a significant negative relationship between value internalization and aggressiveness (r = -0.599, p < 0.05). This finding indicates that the higher the level of internalization of martial arts values, the lower the level of adolescent aggressiveness. The implication of the results of this study shows the importance of the role of pencak silat institutions in shaping the character of adolescents who are more adaptive and emotionally controlled through strengthening the values of their teachings.Tingginya kecenderungan perilaku agresif pada remaja menjadi isu yang perlu mendapat perhatian, terutama ketika nilai-nilai positif tidak tertanam secara kuat dalam diri individu. Dalam konteks ini, nilai ajaran perguruan silat IKS.PI Kera Sakti berpotensi menjadi salah satu sumber pembentukan karakter yang positif. Penelitian ini bertujuan untuk menguji hubungan antara internalisasi nilai ajaran perguruan silat IKS.PI Kera Sakti dengan tingkat agresivitas pada remaja. Pendekatan yang digunakan adalah kuantitatif dengan subjek sebanyak 63 remaja anggota aktif perguruan silat tersebut. Teknik pengambilan sampel menggunakan Purposive Sampling. Metode pengumpulan data dilakukan menggunakan skala internalisasi nilai dan skala agresivitas. Data yang telah dikumpulkan kemudian dianalisis dengan uji analisis Pearson Product Moment. Hasil penelitian menunjukkan nilai korelasi Pearson sebesar -0.599 dengan nilai signifikansi 0.000 (p<0.05). Analisis data menunjukkan adanya hubungan negatif yang signifikan antara internalisasi nilai dengan agresivitas (r = -0.599, p < 0.05). Temuan ini menunjukkan bahwa semakin tinggi tingkat internalisasi nilai ajaran perguruan silat, maka semakin rendah tingkat agresivitas remaja. Implikasi dari hasil penelitian ini menunjukkan pentingnya peran lembaga pencak silat dalam membentuk karakter remaja yang lebih adaptif dan terkendali secara emosional melalui penguatan nilai-nilai ajaran yang mereka miliki.